Production of Biolubricants from Balanites aegyptiaca Seed Oil via Epoxidation and Double Transesterification Techniques - M. Usman; H. Ibrahim; E. B. Agbaji (Journal of Applied Sciences and Environmental Management, 2023)
In this study, Balanites aegyptiaca seed oil was extracted from the ground seed using the Soxhlet extraction method with n-hexane as the extraction solvent to produce two biolubricants; one via epoxidation to produce Balanites aegyptiaca Lubricant (BAB-E) and the other via transesterification with trimethylolpropane to produce Balanites aegyptiaca Lubricant (BAB-T). Both biolubricants were characterized using Fourier Transform Infrared Spectrometry. The physicochemical properties, lubricity and thermal properties of the produced biolubricants were determined. Results showed that the biolubricants had wavelengths of 3008.0 cm-1 associated with C-H stretching, 2922.8 cm-1 to -OH (acid), 1740.7 cm-1 to C=O, 1488.8 cm-1 to C=C stretching, 1364.2 cm-1 to NO2, 1237.6 cm-1 to C-O, 1159.2 cm-1 to C-C and 723.1 cm-1 to C-H bending. BAB-T had viscosities of 58.29 and 10.36 cSt at 40 and 100 OC respectively while those of BAB-E were 54.37 and 9.56 cSt. They had viscosity index of 168 and 161, and pour points of -9 and -8 respectively. These values were observed to be within acceptable range. BAB-T had coefficient of friction of 0.094 ± 0.014 while that of BAB-E was 0.080 ± 0.010 respectively. The biolubricants were observed to have thermal stability and showed properties similar to those of lubricants and show remarkable potentials to be used as alternatives to fossil-based lubricants.